A spectral method of the analysis of linear control systems - Kurdyukov, Alexander P.; Boichenko, Victor A. (Zielona Góra: Uniwersytet Zielonogórski)
A spectral method of the analysis of linear control systems is considered. Within the framework of this approach the [sigma]-entropy of input signals and the [sigma]-entropy norm of systems are introduced. The invariance of the introduced norm makes it possible to get invariant results of [sigma]-entropy analysis.
Keywords: anisotropy-based control theory; anisotropic norm